2013
DOI: 10.1590/s0036-46652013000200006
|View full text |Cite
|
Sign up to set email alerts
|

USE OF THE POLYMERASE CHAIN REACTION FOR THE DIAGNOSIS OF ASYMPTOMATIC Leishmania INFECTION IN A VISCERAL LEISHMANIASIS-ENDEMIC AREA

Abstract: The diagnosis of asymptomatic infection with Leishmania (Leishmania) chagasi has become more important over recent years. Expansion of visceral leishmaniasis might be associated with other routes of transmission such as transfusion, congenital or even vector transmission, and subjects with asymptomatic infection are potential reservoirs. Moreover, the identification of infection may contribute to the management of patients with immunosuppressive conditions (HIV, transplants, use of immunomodulators) and to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…11 However, the utility of PCR in asymptomatic HIV-co-infected patients may be of limited use because the detection of Leishmania is not always correlated with clinical disease. 33,34 In the same period, a total of six cases of symptomatic visceral leishmaniasis were confirmed by our laboratory (incidence: 0.95 cases per 100 000 inhabitants), three of the cases were found in immusuppressed patients with no documented HIV infection (one patient with ulcerative colitis treated with infliximab, one patient with giant cell arteritis treated with prednisone, and one patient with brain metastases treated with dexamethasone), and the remaining three cases occurred in patients with HIV infection and symptomatic visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, the utility of PCR in asymptomatic HIV-co-infected patients may be of limited use because the detection of Leishmania is not always correlated with clinical disease. 33,34 In the same period, a total of six cases of symptomatic visceral leishmaniasis were confirmed by our laboratory (incidence: 0.95 cases per 100 000 inhabitants), three of the cases were found in immusuppressed patients with no documented HIV infection (one patient with ulcerative colitis treated with infliximab, one patient with giant cell arteritis treated with prednisone, and one patient with brain metastases treated with dexamethasone), and the remaining three cases occurred in patients with HIV infection and symptomatic visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…No association was observed between the results of PCR, serological and skin tests. The authors concluded that a positive PCR result in subjects from the endemic area does not indicate a risk of progression to VL, nor is it associated with a positive result in the serological tests [58].…”
Section: Asymptomatic Cases Of Leishmania Infection and Studies On Blmentioning
confidence: 99%
“…The assessment of the risk resulting from latent infection is, however, problematic as a positive blood PCR in an asymptomatic individual may not necessarily signify the presence of live parasites. PCR positivity may occasionally persist for many months after successful therapy even in immunocompetent patients and may represent a resolved clinical or subclinical infection . Also there is a concern of cross‐reactivity with Trypanosoma cruzi with use of some primers …”
Section: Solid Organ Transplant Recipientsmentioning
confidence: 99%